Simulation of Plasmaspheric Plume Impact on Dayside Magnetic Reconnection. Issue 4 (20th February 2020) - Dargent, J.; Aunai, N.; Lavraud, B.; Toledo‐Redondo, S.; Califano, F.
Abstract: During periods of strong magnetic activity, cold dense plasma from the plasmasphere typically forms a plume extending toward the dayside magnetopause, eventually reaching it. In this work, we present a large‐scale two‐dimensional fully kinetic particle‐in‐cell simulation of a reconnecting magnetopause hit by a propagating plasmaspheric plume. The simulation is designed so that it undergoes four distinct phases: initial unsteady state, steady state prior to plume arrival at the magnetospause, plume interaction, and steady state once the plume is well engulfed in the reconnection site. We show the evolution of the magnetopause's dynamics subjected to the modification of the inflowing plasma. Our main result is that the change in the plasma temperature (cold protons in the plume) has no effects on the magnetic reconnection rate, which on average depends only on the inflowing magnetic field and total ion density, before, during, and after the impact. Key Points: We run particle‐in‐cell simulation of asymmetric magnetic reconnection including the impact of a cold plasmaspheric plume The impact of the plume reduces the reconnection rate following Magnetohydrodynamics scaling laws due to mass loading only The cold temperature of the plume does not influence the reconnection rate